Kehidupan Hewan dalam Relief Candi Bumiayu - Rizqy Prayoga; Hudaidah Hudaidah (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the iconographic program of faunal and mythological figures found in the Candi Bumi Ayu temple complex, South Sumatra. As the only major Hindu-Shaivite site from the classical period in the region, active between the 9th and 13th centuries AD, its artistic representations offer a unique perspective on the religious and cultural dynamics within the Srivijayan sphere of influence. Through a descriptive-analytical method, this paper examines thirteen specific iconographic elements, including the Kala head, Makara, Nandi, Gana, and various faunal reliefs. The findings indicate that these figures are not merely decorative but constitute a coherent symbolic system with three primary functions: apotropaic (guarding sacred space), theological (representing the divine presence of Shiva and his retinue), and cultural (articulating a distinct local Sumatran artistic canon). This local style, while in dialogue with Javanese and Indic traditions, demonstrates significant innovation, particularly in the depiction of the Kala head and the figures within the Makara's mouth. This research concludes that the animal and mythological iconography of Candi Bumi Ayu is a sophisticated visual text that reveals a complex interplay of religious cosmology, ritual practice, and the assertion of a unique regional identity.